Syariah-Compliant Financing Models and Their Strategic Contribution to the Agricultural Sector and the Development of Micro, Small, and Medium Enterprises (MSMEs) - Ali Hardana; Alif Sepriadi; Meylika Nadya; Regitra Ingka Cahyani; Bunga Kartika (CV. Get Press Indonesia, 2025)
This study examines how Islamic financing models, like murabahah and salam, impact Indonesia's agricultural and MSME sectors. Using 2023 national data and Structural Equation Modeling (SEM), the research finds that Islamic financing has a significant positive effect on sector performance, boosting productivity and revenue. This improved performance, in turn, acts as a key link to broader strategic contributions, such as MSME growth and improved welfare. The findings suggest that Islamic finance is crucial for inclusive economic development and that policies should be tailored to different regions and business scales to maximize its impact.